Effect of Fibrin-Like Stimulators on the Activation of Plasminogen by Tissue-Type Plasminogen Activator (t-PA) - Studies with Active Site Mutagenized Plasminogen and Plasmin Resistant t-PA - Lijnen, H R; Van Hoet, B; De Cock, F; Collen, D (Thrombosis and Haemostasis, 1990)
The activation of plasminogen by t-PA was measured in the presence and absence of fibrin stimulation, using natural human plasminogen (nPlg) and rPlg-Ala740, a recombinant plasminogen with the active site Ser740 mutagenaed to Ala. Recombinant wild type t-PA (rt-PA) was used as well as rt-PA -Glul275, a recombinant single chain t-PA in which the Arg of the plasmin sensitiv e Arg275- Ile276 peptide bond was substituted with Glu. Conversion of 125I-labeled single chain plasminogen to two-chain plasmin by wild-type or mutant t-PA, was quantitated by SDS gel electrophoresis and radioisotope counting of gel slices, and expressed as initial activation rates (v0 in pM s−1) per 1 μM enzyme. In the absence of fibrin stimulation, the vs for the activation of nPlg and rPlg-Ala740 with the single chain forms of both t-PAs were comparable (0.6 to 2.7 pM s−1) but were lower than with the corresponding two-chain forms (5.3 to 23 pM s−1). In the presence of 1 μM soluble fibrin monomer (desAAfibrin), the v0 for nPlg and rPlg-Ala740 by single chain rt-PA was also comparable (24 and, 33 pM s-1 respectively), whereas with 1 pM CNBr-digested fibrinogen, the vs for nPlg with single chain rt-PA was about 20-fold higher than that of rPlg-Ala740 (135 and 7.5 pM s−1 respectively). In contrast, the vs for nPlg and rPlg-Ala740 by single chain rt-PA- G1u275, two-chain rt-PA-G1u275 or two-chain rt-PA were comparable in the presence of either desAAfibrin or CNBr-digested fibrinogen.These findings confirm and establish: 1) that single chain t-PA is an active enzyme both in the presence and absence of fibrin stimulator; 2) that, in a system devoid of plasmin activity (rPlg- Ala740), the two-chain form of t-PA is about L5 times more active than the single chain form in the absence of fibrin but equipotent in the presence of desAAfibrin; and 3) that the mechanism of stimulation of plasminogen activation with single chain t-PA by CNBr-digested fibrinogen is different from that by soluble fibrin.